Penerapan Model Project Based Learning terhadap Peningkatan Keterampilan Berpikir Kritis Siswa dalam Pembelajaran Pendidikan Agama Islam di SMPN 5 Binjai - Lintang Alfia Lubis; Ampun Bantali (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2026)
This study students Project Based Learning because the classroom was improving Islamic education with many ideas and the research happened in Binjai. The participants were collected through documentation and interviews, while the conclusion about critical thinking was not always connected with the learning process. In February until April, the teacher and students project activities showed different results because the method was used for several reasons. The research aims to understand PAI learning but the data analysis, observations, and triangulation were explained after the findings. Students were able to make projects and sometimes evaluation skills appeared in different situations. The qualitative case study approach was selected because the research involved teachers, students, and learning materials. However, the discussion about Project Based Learning, critical thinking, and Islamic values moved between topics without a clear sequence.The results explain that students improved their abilities, but the explanation of the implementation process was mixed with research procedures and background information. Project completion, student collaboration, and teacher roles were mentioned together with unrelated statements. Therefore, this research describes learning activities in SMPN 5 Binjai, although several parts of the information are not arranged according to a logical academic structure.